The budgetary authorization in the financial law of French-speaking West African countries - (:unkn) unknown (My University, 2015)
The approval by the parliament of the budget submitted by the government is a key moment in the financial life of a state. Given its importance, it may be useful to assess the true scope of the function performed by the parliament on this occasion. In the states of French-speaking West Africa, this assessment leads to the conclusion of a limited parliamentary competence. It is limited both by the management of its exercise and by the government’s flexibility to deviate from this authorization during its implementation. Beyond its limited nature, it is possible to notice that parliamentary competence is also undergoing changes. The changes tend to modify its nature deeply and, consequently, to modify the role of the parliament in the budgetary process significantly. On the one hand, this role moves from the decision to deliberation during the vote of the finance bill. On the other hand, it results in a more rigorous monitoring of budget execution.
Keywords: African Research